2007
DOI: 10.1111/j.1540-6237.2007.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Branded: The Economic Geographies of Streets Named in Honor of Reverend Dr. Martin Luther King, Jr.*

Abstract: We investigate the economic geographies of streets named for Reverend Dr. Martin Luther King, Jr. (MLK Streets), which are an increasingly common means by which various community members across the United States are attempting to commemorate the slain civil rights leader. It is our intent to characterize these negatively "branded" spaces in order to challenge some of the common perceptions about them and inform current and future MLK Street naming debates. Copyright (c) 2007 Southwestern Social Science Associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…The example of the MAP's public meetings reinforces the point. As a place, Muncie has a set of historic and geographic contexts that affect the exercise of agency (e.g., Pred 1984), which includes race-and class-based residential patterns that continue to divide the city functionally and perceptually (Mitchelson, Alderman, and Popke 2007;MAP 2010). Despite the fact that these patterns are well known and understood by many residents, including the prominent citizens that make up the MAP board, the initial meeting locations reflected no concern for this context.…”
Section: Discussionmentioning
confidence: 99%
“…The example of the MAP's public meetings reinforces the point. As a place, Muncie has a set of historic and geographic contexts that affect the exercise of agency (e.g., Pred 1984), which includes race-and class-based residential patterns that continue to divide the city functionally and perceptually (Mitchelson, Alderman, and Popke 2007;MAP 2010). Despite the fact that these patterns are well known and understood by many residents, including the prominent citizens that make up the MAP board, the initial meeting locations reflected no concern for this context.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, however, critical geographers have used this work productively, placing a special emphasis on space and location (Foote and Azaryahu 2007;Alderman 2002Alderman , 2003Mitchelson et al 2007;Yeoh 1992Yeoh , 1996; and on state socialist Europe, see Azaryahu 1996Azaryahu , 1997Gill 2005;Light et al 2002;Light 2000Light , 2004. Furthermore, in the case of Hungary and Budapest there have been a number of studies on street names, statues, and memorials (c.f.…”
Section: Introductionmentioning
confidence: 96%
“…In "Branded," a recent study of 777 King streets, Mitchelson et al (2007) found that "the negative branding of King Streets is largely mythical; in much of the country, there is no real difference between what we find on primarily commercial King Streets and other categories of urban space" (p. 142). Even though this study depends almost exclusively on economic development and employment figures for its conclusions, with conspicuous analytical absences of socio-cultural indicators such as community organizations, crime statistics, and dedicated social spaces (playgrounds, parks, and et cetera), it demonstrates that the memory of African American spaces, especially King streets, is not entirely accurate, yet it is the information stock that prevails in public communication (i.e., newspapers, comedy clubs, and everyday conversations) that stubbornly articulates what Mitchelson et al call a "sociocultural process of negative 'branding'" (p. 142).…”
Section: Sites Of Commemoration and The Negotiation Of Alternative Rementioning
confidence: 91%